Immunotherapy for Bladder Cancer: Latest Advances and Ongoing Clinical Trials. (17th November 2022) - Ward Grados, Daniela F.; Ahmadi, Hamed; Griffith, Thomas S; Warlick, Christopher A.
ABSTRACT: For nearly 50 years, immunotherapy has been used in patients with bladder cancer in the form of Mycobacterium bovis Bacillus Calmette-Guerin (BCG), which is still the first-line therapy for non-muscle invasive disease. However, the remarkable results obtained with checkpoint inhibitor drugs, including Pembrolizumab and Atezolizumab, have fueled the quest to optimize these and other forms of immunotherapy for both non-muscle invasive as well as advanced bladder cancer. In this review we summarize the current state of the rapidly evolving field of immunotherapy in bladder cancer highlighting novel approaches and ongoing trials in this exciting area of research.